18S rRNA gene amplicon sequencing combined with culture‐based surveys of maize rhizosphere protists reveal dominant, plant‐enriched and culturable community members. Issue 1 (26th December 2021) - Taerum, Stephen J.; Micciulla, Jamie; Corso, Gabrielle; Steven, Blaire; Gage, Daniel J.; Triplett, Lindsay R.
Summary: Protists play important roles in shaping the microbial community of the rhizosphere and defining these roles will require the study of protist isolates. However, there is still a limited understanding of how well protist isolation efforts can capture the diversity and composition of rhizosphere protistan communities. Here, we report a simultaneous isolation and 18S rRNA gene amplicon sequencing survey describing the protist diversity of maize rhizospheres in two climatically and pedologically distinct sites. We demonstrated that the maize rhizosphere exerted significant and site‐dependent effects on the protistan community structure and defined a set of core and rhizosphere‐enriched protists. From the same root samples, we generated a library of 103 protist isolates representing 46 18S rRNA gene sequence variants from six eukaryotic supergroups. While cultured isolates represented a small proportion of total protist diversity recovered by sequencing, they included taxa enriched in rhizosphere soils across all samples, encompassing 9% of all core sequence variants. The isolation approach also captured 17 protists not detected through 18S rRNA gene amplicon sequencing. This study demonstrated that maize roots select for distinct protistan communities, and established a diverse protist culture collection that can be used for future research linking protists to rhizosphere status and plant health.